PELAKSANAAN PENGAWASAN LINGKUNGAN HIDUP OLEH BADAN LINGKUNGAN HIDUP KOTA PEKANBARU (STUDI KASUS USAHA ATAU KEGIATAN RUMAH SAKIT DI KOTA PEKANBARU) - Purwati, Destri; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
As the capital of Riau province, Pekanbaru city is the central of economy. Trading and service are the main sectors. As the economic grows, environment becomes a big issue. Mishandling of environment will create a big impact.One of the instruments in managing the effects of environment is efforts of environmental management and environmental monitoring efforts (UKL-UPL), every hospital has to have this unit. Unfortunately, it has not beem applied properly. It can be seen from the data belongs to Environment Agency Pekanbaru. It said that there are only few that give routines report about the program. This study is aimed to find out the supervision done by Environment Agency to the unit of the hospital in managing and supervising the environment.This is a qualitative descriptive research. Data collecting technique are observation, interview, and documents collected from the informants based on snowball sampling. Writer used supervising theory by Manullang. There are three stage of the supervision, which are; deciding measurement tool (standard) in doing the supervision of the hospital unit, assessing management activity, and monitoring the management activity. Result shows that the supervision by Environment Agency Pekanbaru city to the business unit of hospitals is not maximal yet. The biggest obstacle is internal factor, that there is lack number of officer in Environment Agency, While the external factor is that the doer of the activity only pay a little attention to the activity. Key Word: The Implementation, Supervision, Environment